Exploring the body condition of gray whales (Eschrichtius robustus) through adipocyte analysis during unusual mortality events - Lorena Citlalli Magallón Flores; Lorena Viloria-Gómora; Germán Garrido-Fariña; Pablo Hernández-Almaraz; Simone Antichi; Steven L. Swartz; Jorge Urbán R.; Sergio Martínez-Aguilar (Science of The Total Environment, 2024)

Range-Wide Comparison of Gray Whale Body Condition Reveals Contrasting Sub-Population Health Characteristics and Vulnerability to Environmental Change - Leigh G. Torres; Clara N. Bird; Fabian Rodríguez-González; Fredrik Christiansen; Lars Bejder; Leila Lemos; Jorge Urban R; Steven Swartz; Amy Willoughby; Joshua Hewitt; KC. Bierlich (Frontiers in Marine Science, 2022)
Climate change is a global phenomenon, yet impacts on resource availability to predators may be spatially and temporally diverse and asynchronous. As capital breeders, whales are dependent on dense, predictable prey resources during foraging seasons. An Unusual Mortality Event (UME) of Eastern North Pacific (ENP) gray whales ( Eschrichtius robustus ) was declared in 2019 due to a dramatic rise in stranded animals, many emaciated. Climate change impacts may have affected prey availability on the primary foraging grounds of ENP gray whales (~20,000 individuals) in the Arctic and sub-Arctic region and in coastal habitats between northern California, USA and British Columbia, Canada where a small sub-group of ENP whales called the Pacific Coast Feeding Group (PCFG; ~230 individuals) forages. To investigate variability of gray whale body condition relative to changing ocean conditions, we compare two datasets of gray whale aerial photogrammetry images collected via Unoccupied Aircraft Systems (UAS) on the ENP wintering grounds in San Ignacio Lagoon, Mexico (SIL; n=111) and on the PCFG feeding grounds in Oregon, USA (n=72) over the same three-year period (2017–2019). We document concurrent body condition improvement of PCFG whales in Oregon while body condition of whales in SIL declined. This result indicates that the UME may have affected ENP whales due to reduced energetic gain on some Arctic/sub-Arctic foraging grounds, while PCFG whales are recovering from poor prey conditions during the NE Pacific marine heatwave event of 2014–2016. Surprisingly, we found that PCFG whales in Oregon had significantly worse body condition than whales in SIL, even when accounting for year and phenology. We derive support for this unexpected finding via photogrammetry analysis of opportunistic aerial images of gray whales on Arctic foraging grounds (n=18) compared to PCFG whales in Oregon (n=30): the body condition of PCFG whales was significantly lower (t=2.96, p=0.005), which may cause PCFG whales to have reduced reproductive capacity or resilience to environmental perturbations compared to ENP whales. Overall, our study elucidates divergent gray whale body condition across sub-groups and time, and we demonstrate the value of UAS to effectively monitor and identify the physiological response of whales to climate change.

GENETIC IDENTIFICATION OF AN INDIVIDUAL HUMPBACK WHALE BETWEEN THE EASTERN CARIBBEAN AND THE NORWEGIAN SEA - Martine Bérubé; Mary Beth Rew; Tim Cole; Steven L. Swartz; Eric Zolman; Nils ØIen; Per J. Palsbøll (Marine Mammal Science, 2004)

A FIRST ENCOUNTER WITH KEN NORRIS - Steven L. Swartz (Marine Mammal Science, 1999)